Structural Variety of Defect Perovskite Variants M3E2X9(M = Rb, Tl, E = Bi, Sb, X = Br, I) - Chang, Jen-Hui; Doert, Thomas; Ruck, Michael (Zeitschrift für Anorganische und Allgemeine Chemie, 2016)
The compounds Rb3Sb2Br9, Rb3Sb2I9, Rb3Bi2Br9, Rb3Bi2I9, and Tl3Bi2Br9were synthesized and their crystal structures determined from single crystal X-ray diffraction data. The compounds Rb3Sb2Br9, Rb3Sb2I9, and Rb3Bi2I9crystallize in the Tl3Bi2I9type of structure (space group P21/n, no. 14). Rb3Bi2Br9and Tl3Bi2Br9crystallize in a new but closely related type of structure (space group P21/a, no. 14). Both structure types feature characteristic double layers comprising corner-sharing EX6octahedra. The space groups are set in a way that the stacking direction of the layers is the [001] direction. The group-subgroup relations to cubic perovskite ABO3are discussed. Differences between M3E2X9types are attributed to distortions of the underlying MX3close packing. Depending on the atomic size ratio, the distortions are quantified by an order parameter.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Degree of distortion; Goldschmidt tolerance factor; Perovskite types; Rubidium; Thallium; Sphere close AX